PENGEMBANGAN KREATIVITAS SISWA DALAM PEMBELAJARAN KREATIF PADA MATA PELAJARAN IPAS DI SEKOLAH DASAR - Safitri, Dewi; Fitriyani, Yani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe efforts to develop student creativity through creative learning in the subject of Natural and Social Sciences in elementary schools. The method used in this study uses descriptive qualitative with data collection techniques in the form of observation, interviews, and documentation. The subjects of the study were fifth grade students of SDN 2 Gandasoli. The results of the study indicate that varied learning based on experiments, projects, and the use of interactive media has proven effective in developing student creativity in schools. The main factors in supporting student creativity are innovative learning methods, and a supportive learning environment, while the inhibiting factors include limited facilities and infrastructure, lack of teacher training, and an overly dense curriculum. It can be concluded that creative learning in Natural Sciences has an important role in encouraging the development of student creativity in elementary schools.